Biochemical and genotoxic effects of a commercial formulation of the herbicide tebuthiuron in Oreochromis niloticus of different sizes - Bernardes, Mariana Furio Franco [UNESP]; Maschio, Lucilene Regina [UNESP]; Oliveira, Maria Tercilia V A [UNESP]; Almeida, Eduardo A. [UNESP] (Ecototoxicology and Environmental Contamination, 2014)
Pesticides are serious contaminants because they are designed to eliminate pests, but they also affect non-target species. The present study aimed to evaluate the biochemical and genetic effects of the herbicide tebuthiuron in Oreochromis niloticus of different sizes. Thus, we analyzed biomarkers in small and large O. niloticus specimens exposed to 62.5, 125 and 250 mg L-1 of tebuthiuron for 72 hours. Fish exposed to 250 mg L-1 had high mortality rates; therefore, the data could not be used. The results showed an increase in EROD activity in fish exposed to 125 mg L-1, but no GST alteration. Antioxidant enzymes GPx and CAT were altered only in the liver of treated fish compared to the control group: CAT decreased in large fish, and GPx increased in small fish. The MDA analysis did not evidence lipid peroxidation. High DNA damage in exposed small fish (not in large fish) was observed using comet assay, but a micronucleus test did not show mutagenicity. Moreover, a comparison between control groups with specimens of different sizes revealed that small fish are more susceptible than large fish to the tebuthiuron effects, since increased comet scores was observed only for smaller fish.
Keywords: aquatic toxicology; biomarkers; ecotoxicology; fish; pesticide